Stakeholder theory: Exploring systems-theoretic and process-philosophic connections - Vladislav Valentinov; Steffen Roth (Systems Research and Behavioral Science, 2024)
Modern stakeholder theory is premised on the `integration thesis', according to which business and ethics constitute an inseparable unity. For many management scholars, this thesis raised the difficult question of how far business can pursue ethical goals without losing its functional autonomy. We address this question by interpreting the integration thesis as the Luhmannian `unity of difference' of business and ethics. This interpretation allows business and ethics to remain conceptually distinct, yet takes their very distinction to constitute a logical and dialectical unity as envisioned by the integration thesis. To justify this interpretation, we draw on the Luhmannian systems theory which accentuates the precariousness of the environment faced by business corporations, and on process philosophy which underscores the unique human capacity to navigate this precariousness by following social norms of ethical behaviour. We argue that a key prerequisite of successful stakeholder management is the activation of this human capacity.
Keywords: 300; integration thesis; process philosophy; stakeholder theory; systems theory